การบริหารความเสี่ยงของโรงแรมในจังหวัดเชียงใหม่ - กมลชนก อนุกูล (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2017)
This independent study aimed to examine risk management in the hotel industry in Chiang Mai province by means of COSO ERM’s eight-component (Enterprise Risk Management) framework. Data were collected through a questionnaire, of which respondents were general managers, department managers in charge of operations, or hotel executives whose responsibility included risk management. The said questionnaire was distributed to 183 hotels in Chiang Mai, and 140 pieces of data were collected in this regard. Afterwards, the data were processed and analyzed using descriptive statistics; namely frequency, percentage, and mean. It was found that the majority of the respondents was female, aged between 31-40 years old, holding posts of department manager and executives without business ownership. The responsive businesses were company limited with up to 50 employees; 5-30 million Baht in registered capital; over 200 million-Baht in total assets; over 30 million Baht in total annual sales; 1-5 and 6-10 million baht respectively in net profit after tax; and over 10 years of establishment. With regard to COSO ERM’s eight-component framework, it was found that the majority of the respondents’ implementation of overall risk management framework was at a high level. Identification risk event component was utilized most, achieved in a form of policies to constantly improve and develop the businesses in order to enhance competitiveness. The second and third most utilized components were Objective Setting, executed by having each department set its clear goals; and Internal Environment, achieved by means of human resources management with a focus on integrity and ethical values. On the other hand, the least utilized component was Risk Responses, achieved via a policy to recruit hotel executives at the international level. As for the Operational Risk Management, it was discovered that the implementation of overall operational risk management framework among the majority of the respondents was at a high level. In this connection, of the four aspects of operational risk source management, the most tackled aspect was people risk management. This was achieved by means of sufficient staffing especially during high seasons. The second most tackled aspect was process risk management, which was handled by apparent and appropriate division of labor among personnel at different levels and departments. The next most tackled aspect was external risk management. This was covered by means of asset insurance against losses from unexpected events or natural disasters as well as when the business comes to a halt. Meanwhile, the least tackled aspect was technology risk management, which was resolved by means of responsive handbooks and guidebooks as well as training on the use of relevant programs and systems.